Study of a solar energy drying system—Energy savings and effect in dried food quality - Pereira, Carlos (2022)
It is estimated that in Portugal per year, 132 kg/person of food is wasted due to imperfections in weight, shape and due to their perishability, resulting in foods that cannot be marketed. Solar drying can be used to extend food life. However, it usually does not meet the current productivity and quality requirements of the dried product. Solar energy is renewable, very available in Portugal, which can make an important contribution to reducing the specific energy consumption and carbon footprint intensity associated with drying. This work aims to optimize the drying process using a solar dryer with electric support. The conditions of temperature and humidity in the dryer and their influence on the physical and chemical properties of blueberries and raspberries were studied, namely the ash, protein, fat, sugars, total phenolic compounds content and antioxidant capacity. It was concluded that the blueberries and raspberries, after drying underwent slight changes in some chemical parameters, namely the reduction of fats and phenolic compounds. The results of the drying tests showed a strong dependence on atmospheric conditions. Under the most favorable conditions, it was possible to record reductions in electricity consumption of 35%.